1997
DOI: 10.1002/(sici)1520-6866(1997)17:4/5<285::aid-tcm11>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of the toxic equivalency factor approach for risk assessment of TCDD and related compounds

Abstract: Halogenated aromatic hydrocarbons (HAHs), such as polychlorinated biphenyls (PCBs), dibenzo‐ρ‐dioxins (PCDDs), and dibenzofurans (PCDFs), are industrial compounds or by‐products that have been widely identified as environmental contaminants. Hazard and risk assessment of complex HAH mixtures have utilized a toxic equivalency factor (TEF) approach, where the toxic equivalents (TEQs) of any mixture are equal to the sum of the concentration of individual (i) congeners times their potencies (TEFi) relative to 2,3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(41 citation statements)
references
References 94 publications
(115 reference statements)
2
39
0
Order By: Relevance
“…Consequently, two possible explanations may contribute to our understanding of the mechanisms responsible for this nonadditive interaction: a) TCDD and PHAH (such as PCB77 and PCB153) might bind to different receptors and act through a different mechanism of action, therefore, the combined effects showed significantly non-additive interaction; b) TCDD and related PHAH (such as TCDF, PCB126) probably bind to the same Ah-receptor but act at different sites and induce different conformations of the Ahreceptor complex which exhibit different activities as nuclear transcription factors. The interactions of both potent and weak Ah receptor agonists to give nonadditive interactions has previously been reported from multiple laboratories and summarised in a recent review (Safe 1998). The non-additive antagonistic interactions between various PHAH are also consistent with results obtained for other ligand-induced transcription factors such as the estrogen receptor (ER) where PHAH such as PCB153: exhibit tissue specific weak ER aginist/antagonist activities (Ashby et al 1997;Gaido et al 1997;Ramamoorthy et al 1997).…”
Section: Resultssupporting
confidence: 59%
“…Consequently, two possible explanations may contribute to our understanding of the mechanisms responsible for this nonadditive interaction: a) TCDD and PHAH (such as PCB77 and PCB153) might bind to different receptors and act through a different mechanism of action, therefore, the combined effects showed significantly non-additive interaction; b) TCDD and related PHAH (such as TCDF, PCB126) probably bind to the same Ah-receptor but act at different sites and induce different conformations of the Ahreceptor complex which exhibit different activities as nuclear transcription factors. The interactions of both potent and weak Ah receptor agonists to give nonadditive interactions has previously been reported from multiple laboratories and summarised in a recent review (Safe 1998). The non-additive antagonistic interactions between various PHAH are also consistent with results obtained for other ligand-induced transcription factors such as the estrogen receptor (ER) where PHAH such as PCB153: exhibit tissue specific weak ER aginist/antagonist activities (Ashby et al 1997;Gaido et al 1997;Ramamoorthy et al 1997).…”
Section: Resultssupporting
confidence: 59%
“…In our experiment, the MNU-TCDD treatment involved the administration of 87.5 ng TCDD (or 2.5 µg/kg bw) at day 18, and this did not inhibit tumor development. Three times less TCDD-toxic equivalents [TEQ (90,91)] were administered to the MNU-1,000× group (31.44 ng TCDD-TEQ divided in five doses over the first 20 days of life) than with the MNU-TCDD treatment, yet the MNU-1,000× group showed delayed tumor development. [The TCDD-TEQ value for the mixture was calculated using the mean volume of the mixture administered to the rats, the content of our mixture in Ah-R agonists, and their toxic equivalency factors (TEF) (PCB #77, 0.0001; #126, 0.1; #169, 0.01; #118, 0.0001; #156, 0.0005; #170, 0.0001, #180, 0.00005 (92)].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that TCDD exposure results in antiestrogenic activity and a!ects hormonal systems, but does not bind to estrogen receptors (Safe, 1998). Observed e!ects include delayed testis descent, impaired spermatogenic function, decreased accessory sex gland weights, and feminization of male sexual behavior (EPA, 1997;Solla et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…At present, because of the extreme toxicity and high cost of developing standards, most studies on TCDD toxicity have involved short-term or one-time exposure (Mehrle et al, 1988;Wisk and Cooper, 1990;Spitsbergen et al, 1991;Walker et al, 1994;Cantrell et al, 1996;Henry et al, 1997;Elonen et al, 1998;Hornung et al, 1999). Therefore information on the relationship between EROD activity and TCDD exposure in di!erent developmental stages during long-term exposure to low dosage TCDD is lacking.It has been reported that TCDD exposure results in antiestrogenic activity and a!ects hormonal systems, but does not bind to estrogen receptors (Safe, 1998). Observed e!ects include delayed testis descent, impaired spermatogenic function, decreased accessory sex gland weights, and feminization of male sexual behavior (EPA, 1997;Solla et al, 1998).…”
mentioning
confidence: 99%